Río de la Plata estuary response to wind variability in synoptic to intraseasonal scales: Barotropic response - Simionato, C.G. (2006)
Fil:Simionato, C.G. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina.